2016
DOI: 10.3201/eid2212.160472
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Host Susceptibility to Heartland Virus

Abstract: Virus-infected Ag129 mice could be a useful model for identifying tick infection or virus transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 39 publications
6
46
0
1
Order By: Relevance
“…AG129 mice, which are devoid of IFN-α/β and γ receptors, were the only animals found to be highly susceptible to disease by the same strain (MO-4) of the virus used in our studies, with 80% lethality observed at a challenge dose of 10 PFU (Bosco-Lauth et al, 2016). Hematologic analysis was not performed in the AG129 mouse model and histopathologic lesions were limited to increased numbers of mononuclear cells in the spleen.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…AG129 mice, which are devoid of IFN-α/β and γ receptors, were the only animals found to be highly susceptible to disease by the same strain (MO-4) of the virus used in our studies, with 80% lethality observed at a challenge dose of 10 PFU (Bosco-Lauth et al, 2016). Hematologic analysis was not performed in the AG129 mouse model and histopathologic lesions were limited to increased numbers of mononuclear cells in the spleen.…”
Section: Discussionmentioning
confidence: 82%
“…Wild-type golden Syrian hamsters are refractory to disease and develop no detectable viremia following HRTV challenge (Bosco-Lauth et al, 2016). To investigate whether STAT2 deficiency would render hamsters susceptible to HRTV, STAT2 KO hamsters (n=4/group) were inoculated with serial dilutions of virus (50,000, 5,000, 500 or 50 CCID 50 ) or sham-infected and observed for signs of illness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,9 Experimental HRTV infections have been attempted in raccoons, goats, chickens, rabbits, hamsters, C57BL/6 mice, and Ag129 mice. 10 None of these species developed detectable viremia or pathologic changes with the exception of Ag129 mice, which are interferon α/β/γ receptor deficient. 10 Several factors suggest WTD could be a host for HRTV, including the detection of seropositive WTD, 8 the likelihood of A. americanum to feed on deer, 11 and the high density and widespread geographic range of WTD populations.…”
mentioning
confidence: 99%
“…HRTV Bunyaviridae ailesinin beş cinsinden biri olup, dünyanın hemen her yerinde görülen Flebovirüs cinsine ait bir patojendir. İlk olarak 2009 yılında, Missouri'de (ABD) lökopeni ve trombositopenisi olan iki çiftçiden izole edilmiştir (7) . Daha sonra Amblyomma americanum türü sert kenelerin bu virüsü taşıdığı gösterilmiştir (8) .…”
Section: Heartland Virüs (Hrtv)unclassified